Scrub Typhus Pathogenesis: Innate Immune Response and Lung Injury During Orientia tsutsugamushi Infection - Trent, Brandon; Fisher, James; Soong, Lynn (Frontiers in Microbiology, 2019)
Scrub typhus is an understudied, potentially lethal disease caused by infection with Orientia tsutsugamushi. Despite causing an estimated 1 million cases per year and an increasing global presence, mechanisms of scrub typhus pathogenesis remain unclear. One of the most life-threatening conditions that can arise in scrub typhus patients is acute respiratory distress syndrome (ARDS). The development of ARDS is a complex process; some of its pathological hallmarks, including prolonged recruitment of inflammatory immune cells to the lung and vasculature damage, have been observed in humans and/or animal models of O. tsutsugamushi infection. Although different cell types and mechanisms may contribute to ARDS development during O. tsutsugamushi infection, this review highlights our current evidence of pulmonary endothelial activation and damage, the potential roles of neutrophils and macrophages in the lung, and the knowledge gaps in this field. Continued investigation of the lung microenvironment and cellular interactions will help elucidate disease pathogenesis and possible treatment during scrub typhus.